Evaluation of leaf extract of Lantana camara aginast seed mycoflora - biopesticides approach - Pawar, P V; A, Bangar M; Muley, S M (International Multidisciplinary Research Journal, 2012)
The Seed treatment with pant extract of Lantana camara does not have any adverse effect on the germinated of seeds even after the treatment for 30 minutes. The seed were treated with aqneous extract, alcoholic extract, and ethyl acetate extract of Lantana camara leavers for 5 minutes, 15 minutes and 30 minutes. It is evident that the treatment of ethyl acetate extract for 30 minutes inhibited the growth of dominant fungi like curvularia lunata A.flavus, A.niger and fusarium moniliforme. So the ethylacetate extract of leaves of Lantana camara can be utilised for the biological control of seeds borne fungi of soybean. So the seed treatment of plant extract will not cause any problem of pollution and the chemical of plant extracts are easily degraded in the soil, So the plant extract of Lantana camara can be used as biopesticide.